AWARENESS ABOUT LOW BACK PAIN AMONG DENTISTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Musculoskeletal disorders have increased progressively due to various etiological factors. Several occupational factors have been accepted as causatives of these disorders. In dentists, constrained and inconvenient spinal positions for back pain, repetitive postures for neck and shoulder pain, and stress are considered the common causative factors for back, cervical, and shoulder complaints. Lower back pain (LBP) is a serious occupational hazard affecting dentists. This survey was performed with the purpose of assessing the awareness of lower back pain and their remedial measures among dentists. A cross-sectional survey was done with a self-administered questionnaire with 10 questions circulated among 100 middle-aged dentists aged between 35 and 50 years. The questionnaire involved information on lower back pain. The responses were recorded and analyzed. 89% of the respondents were aware of the dangerous effects of lower back pain . 60 % said lower back pain is because of excessive bending, 6% said because of wrong sitting posture, and 34% said because of wrong standing posture during treatment . 84 % feel four-handed dentistry can reduce the incidence of lower back pain . 65% of the respondents have some kind of low back pain. 45% said analgesics as treatment for lower back pain, 30% said physiotherapy, and 25% said exercise as the management for lower back pain . There is an adequate amount of awareness among dentists regarding low back pain. Many are suffering from it; increased therapeutic programs should be undertaken to treat this problem.